PENGARUH AKAD IJARAH TERHADAP PERTUMBUHAN DAN STABILITAS INDUSTRI KEUANGAN SYARIAH - Naila Hindana Zulfa; Puteri Chika Aulia; M. Masrukhan (Cahaya Ilmu Bangsa, 2024)
All forms of business carried out by individuals are inseparable from ijarah contracts (lease agreements). The application of ijarah contracts in business activities in the form of leasing land, buildings, services, and others. In business activities, problems often arise related to ijarah contracts, as well as Islamic banks. In the context of the demand for Islamic finance. Akad Ijarah allows users to rent out certain assets within a certain time, with a fee to be paid as rent. In the Islamic finance industry, Akad Ijarah is used in various products and services, such as banking, leasing, and investment. Several studies have evaluated the effect of various types of financing, including Ijarah, on the profitability and cash adequacy of Islamic financial institutions. The results of this study indicate that Ijarah funding has a beneficial impact on the profitability and stability of the Islamic financial sector.